2011
DOI: 10.1021/jp110873t
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Stoichiometry of Water in Proton Hydration and Proton Dehydration Reactions in CH3CN/H2O Solutions

Abstract: Gradual solvation of protons by water is observed in liquids by mixing strong mineral acids with various amounts of water in acetonitrile solutions, a process which promotes rapid dissociation of the acids in these solutions. The stoichiometry of the reaction XH(+) + n(H(2)O) = X + (H(2)O)(n)H(+) was studied for strong mineral acids (negatively charged X, X = ClO(4)¯, Cl¯, Br¯, I¯, CF(3)SO(3)¯) and for strong cationic acids (uncharged X, X = R*NH(2), H(2)O). We have found by direct quantitative analysis prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 121 publications
2
60
0
Order By: Relevance
“…Using exclusively straight-forward but elaborate analytic procedures they argued that in acetonitrile-water solutions the proton forms well defined protonated water clusters within the acetonitrile solvent and suggested that H + 9 O 4 is by far the most stable protonated water cluster in acetonitrile. However, the analytic procedure has been brought to question by the Ikeda group [102] who demonstrated that HClO 4 is not as strong an acid in pure (dry) acetonitrile as assumed by Kolthoff and Chantooni and that traces of acetic acid introduced in the drying procedure of acetonitrile must have affected the analytic procedure used by Kolthoff and Chantooni. Following the general ideas of Kolthoff and Chantooni and using combination of analytic and FTIR techniques not utilized by Kolthoff and Chantooni we have been able to demonstrate that small protonated water solvates are indeed formed in acetonitrile-water mixtures by the dissociation of strong mineral acids such as triflic acid CF 3 SO 4 H. Using FTIR we have been able to show that CF 3 SO 4 H completely ionizes in acetonitrile/water solutions from about 1 : 1 molar ratio of H 2 O : acid [103] and that the cluster size distribution of the protonated water clusters strongly differ from the cluster size distribution deduced indirectly by Kolthoff and Chantooni. We have already reported [103] on the apparent stoichiometry of the aqueous proton in acetonitrile/water solutions as judged by our analytic and spectroscopic analysis. We have found the IR spectra of diluted strong mineral acids in acetonitrile to be relatively insensitive to solvent composition in the 1600-1800 cm −1 spectral range once there were on the average at least 2 water molecules available for solvating all the protons that were present in the acetonitrile solution following the dissociation of strong mineral acids.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Using exclusively straight-forward but elaborate analytic procedures they argued that in acetonitrile-water solutions the proton forms well defined protonated water clusters within the acetonitrile solvent and suggested that H + 9 O 4 is by far the most stable protonated water cluster in acetonitrile. However, the analytic procedure has been brought to question by the Ikeda group [102] who demonstrated that HClO 4 is not as strong an acid in pure (dry) acetonitrile as assumed by Kolthoff and Chantooni and that traces of acetic acid introduced in the drying procedure of acetonitrile must have affected the analytic procedure used by Kolthoff and Chantooni. Following the general ideas of Kolthoff and Chantooni and using combination of analytic and FTIR techniques not utilized by Kolthoff and Chantooni we have been able to demonstrate that small protonated water solvates are indeed formed in acetonitrile-water mixtures by the dissociation of strong mineral acids such as triflic acid CF 3 SO 4 H. Using FTIR we have been able to show that CF 3 SO 4 H completely ionizes in acetonitrile/water solutions from about 1 : 1 molar ratio of H 2 O : acid [103] and that the cluster size distribution of the protonated water clusters strongly differ from the cluster size distribution deduced indirectly by Kolthoff and Chantooni. We have already reported [103] on the apparent stoichiometry of the aqueous proton in acetonitrile/water solutions as judged by our analytic and spectroscopic analysis. We have found the IR spectra of diluted strong mineral acids in acetonitrile to be relatively insensitive to solvent composition in the 1600-1800 cm −1 spectral range once there were on the average at least 2 water molecules available for solvating all the protons that were present in the acetonitrile solution following the dissociation of strong mineral acids.…”
Section: Introductionmentioning
confidence: 80%
“…As we have reported before [103], steady state IR spectra of strong mineral acids in CH 3 CN, was carried out with CaF 2 plates using several optical path lengths, determined by Teflon spacers and adjusted for the concentration of water. Jasco 6300 FTIR instrument was used with 4 cm −1 resolution, with constant N 2 flow to keep low water content in the surrounding atmosphere.…”
Section: Infrared Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation mobility of water molecules is also thought to determine the rate of the Grotthuss conduction mechanism. In bulk water this is known to be the case and the process relies on the cooperative reorientation of a large number (up to [18][19][20] of water molecules. 12,13 In this work we follow a different route to study the effect of confinement of the protonic charge; namely in mixtures of water and a polar but aprotic solvent, acetonitrile (CH3CN or ACN).…”
Section: ) Introductionmentioning
confidence: 99%
“…As a result, the confinement effects on the proton hydration are expected to be large, as has indeed been shown in previous studies. 19,20 We vary the [TfOH]:[H2O] ratio from 1:1 to 1:3, which implies that the number of water molecules available to hydrate the dissociating acid varies, which will strongly influence the hydration structure of the proton. In fact, this is directly evident in the spectra in Fig 1: for [dACN]:[H2O] = 1:1, the center frequency of the O-H stretch band is as low as ~2620 cm -1 , which is strongly red-shifted compared to that of pure water (which is centered at ~3400 cm -1 and represented by the dashed black line in Fig.…”
mentioning
confidence: 99%